The effects of IRF6 rs2235373 polymorphism on mRNA expression changes in non-syndromic cleft lip and palate with various phenotypes - Nasroen, Saskia Lenggogeni; Maskoen, Ani Melani; Soedjana, Hardisiswo; Soeria Soemantri, Eky Setiawan; Hilmanto, Dany (Universitas Padjadjaran, 2018)
Introduction: The IRF6 rs2235373 (C/T) is a polymorphism in the intron region that has been associated with non-syndromic cleft lip and palate (NS CLP) among some populations. Polymorphism in introns can also affect the transcription that should be detected through some changes in IRF6 mRNA expression. This study was aimed to evaluate the effects of IRF6 rs2235373 polymorphism on mRNA expression changes in NS CLP with its phenotypes which include complete unilateral (CU) CLP, complete bilateral (CB) CLP, cleft lip only (CLO), and cleft palate only (CPO). Methods: This study was a laboratory analytical study, using samples from 198 individuals in Indonesia (136 individuals with NS CL/P consisted of CU CLP (n=42), CB CLP (n=34), CLO (n=33), CPO (n=27), and 62 individuals as controls). DNA was extracted from venous blood, and the segment of rs2235373 was evaluated by PCR and Sanger sequencing. mRNA expressions analysis preceded by RNA extraction from oral epithelium, then real-time (RT) PCR was performed. mRNA expression changes were analysed by Livak method and Kruskal Wallis test followed by the Mann Whitney test through CC, GT, and TT genotype. Result: The mRNA expression of TT genotype from NS CU CLP and control was 3.36 higher value than CC genotype (p=0.008), and the mRNA expression of CT genotype from NS CB CLP and control was 0.16 lower value than CC genotype (p=0.000). Conclusion: The IRF6 rs2235373 polymorphism of TT genotype tend to cause mRNA overexpression in NS CU CLP, and CT genotype tend to cause mRNA underexpression in NS CB CLP.Keywords: Non-syndromic cleft lip and palate, NS CLP phenotype, IRF6, rs2235373, mRNA expression.